Circulative biomarkers as predictors of cardiovascular events in patients after treatment of Hodgkin lymphoma - B. B. Samura (Zaporozhye State Medical University, 2017)
Aim. Nature development of lymphoma associates with increased risk of cardiovascular diseases. We aimed to evaluate the prognostic value of circulating NT-proBNP, galectin-3, and VE-cadherin in survivors of Hodgkin lymphoma. Methods: Surveys were given to Hodgkin lymphoma survivors who reached at list partial response after treatment. Observation period was up to 3 years. ELISA method for measurements of circulating level of biomarkers was used. Results: During observation period progression of Hodgkin lymphoma was proved in 8 patients, 4 persons were excluded for poor follow-up. Thirty four cumulative clinical events occurred in 11 patients (55%) within the follow-up, with their distribution being as follows: 2 cardiovascular deaths, 16 cardiac arrhythmias, 6 cardiac ischemic events, 1 stroke, 4 chronic heart failures and 5 hospital admissions for cardiovascular reasons. 4 deaths were not related with cardiovascular pathology or cardiovascular reasons. Circulating level of NT-proBNP in patients without cardiovascular events and with cardiovascular events were 5.81 pg/ml (95% confidence interval [CI] = 3.21-8.41 pg/ml) and 12.74 pg/ml (95 % CI = 6.47-18.94 pg/ml) (р=0.072). In patients without cardiovascular events circulating level of galectin-3 was 5.91 pg/ml (95% confidence interval [CI] = 4.18-7.03 pg/ml) and in patients with cardiovascular events circulating level of galectin-3 was 14.33 pg/ml (95% CI = 5.99-16.18 pg/ml) (р=0.01). Circulating level of VE-cadherin in patients without cardiovascular events and with cardiovascular events were 0.40 pg/ml (95% confidence interval [CI] = 0.31-0.54 pg/ml) and 0.99 pg/ml (95% CI = 0.70-1.15 pg/ml) (р=0.02) In multivariate logistic regression circulating NT-proBNP independently predicted cumulative cardiovascular events (odds ratio [OR] = 1,179; 95% CI = 1,043-1,334; р = 0.008) within 3 years of observation period. Conclusion: Among patients after treatment of Hodgkin lymphoma increased circulating NT-proBNP may associate with increased cumulative cardiovascular events during 3 years.